Stability study of indium tungsten oxide thin‐film transistors annealed under various ambient conditions. Issue 2 (22nd December 2016) - Qu, Mingyue; Chang, Chih‐Hsiang; Meng, Ting; Zhang, Qun; Liu, Po‐Tsun; Shieh, Han‐Ping D.
Abstract : Amorphous tungsten‐doped indium oxide thin‐film transistors (a‐IWO‐TFTs) are prepared by RF sputtering and annealed in air, O2, and N2 ambients. The influence of annealing ambient on the electrical characteristics and stability of the a‐IWO‐TFTs is investigated. It is found that the characteristics and stability are improved in O2 and N2 ambients, which can be explained by the reduction of structural defects and oxygen vacancies. When annealed in O2, the TFT device with saturation mobility of 27.55 cm 2  V −1  s −1, threshold voltage of 0.5 V and drain current on‐off ratio of 10 8 is obtained. After an applied V GS of 25 and −25 V for 2000 s in darkness, the values of Δ V th are 4.5 and −0.92 V, respectively.